Autoevaluación y coevaluación - Chuquitarco Rueda, Sandy Liseth (2016)
This researching work arose from the lack of culture in the implementation of new classroom activities, such as self-assessment and co-assessment, since the heteroevaluation has been applied for some time ago a single strategy to assess learning and being the main instrument the teacher occupies, which is an assessment that is made to a person either work or performance. It is an important into the teaching learning process. This data’s and result that offers and complex by the difficulties involved in prosecuting the actions of people important in teaching process. So implementation of the process of self-assessment and co-assessment of learning was diagnosed by collecting field information that enabled recommend strategies for improving the student’s level basic and secondary school therefore there suitable for this innovative proposal according to the values requires a high degree of confidence of the teacher and the student's responsibility to be part of this educational institution. The teacher assumes the role of transmitter of knowledge and understanding that was tested and evaluated through classical tests. With this traditional process it was to adjust the education system to the culture of truth, establishing strict control of that knowledge, morals and values. Therefore I offer different alternatives to what was the traditional model, both self-assessment and peer assessment is responsible for teacher training and student, to see justifies the student must learn to be autonomous, cooperative and work in groups the teacher as a trainer facilitator of that process. Evaluation is a fundamental active for participation also that a continuous interaction between teachers, students and knowledge they acquire, who is part of the process of teaching and learning, just as motivation promote the values of honesty, respect for all. They are running activities in the institution.